THE SYNERGY OF RHETORIC AND PUBLIC SPEAKING IN CONTEMPORARY ISLAMIC DA'WAH - Mia Fitriah Elkarimah (QAULAN: Journal of Islamic Communication, 2026)
da'wah, arguing that mastery of both competencies is essential for effective, ethical, and impactful religious communication. This research is a literature study employing a qualitative approach through conceptual analysis, drawing exclusively on primary and secondary written sources, including classical rhetorical texts, Qur'anic foundations, and peer-reviewed journal articles, rather than on field observation or empirical data collection. This methodological position was deliberately chosen to enable theoretical synthesis across classical rhetoric, Islamic communication studies, and digital media scholarship. The study integrates classical rhetorical principles, logos, ethos, and pathos with the Islamic communicative foundations of hikmah, mau'izhah hasanah, and jidal bil-latif as articulated in Surah An-Nahl (16:125). The central argument is that rhetoric functions as "strategy," governing message design, structure, and ethical grounding, while public speaking operates as "execution," the practical delivery of that message before an audience. Findings demonstrate that their integration is essential for producing da'i who are intellectually persuasive, emotionally resonant, and socially transformative. Illustrative case analyses of four prominent Indonesian preachers, Ustadz Abdul Somad, Ustadz Adi Hidayat, Gus Baha, and Ustadz Hanan Attaki, reveal how differentiated rhetorical styles operate across scholarly, emotional, and digital registers. The study further highlights that in the digital era, challenges such as shortened attention spans and information overload demand rhetorical recalibration toward concise, multimodal, and contextually sensitive messaging. The findings affirm that integrating rhetoric and public speaking within da'wah training is urgently needed to sustain the relevance and transformative impact of Islamic communication in contemporary society.